(untitled) (Baghdad Science Journal, 2019)
The unpredictable and huge data generation nowadays by smart computing devices like (Sensors, Actuators, Wi-Fi routers), to handle and maintain their computational processing power in real time environment by centralized cloud platform is difficult because of its limitations, issues and challenges, to overcome these, Cisco introduced the Fog computing paradigm as an alternative for cloud-based computing. This recent IT trend is taking the computing experience to the next level. It is an extended and advantageous extension of the centralized cloud computing technology. In this article, we tried to highlight the various issues that currently cloud computing is facing. Here in this research article, we present a comprehensive review of fog computing, differentiating it from cloud computing, also present various use-cases of fog computing in different domains, we came to conclude that Fog computing leads in an efficient energy resource management, leveraging the energy both in terms of consumption and cost scenarios. Further, we highlighted its key features, challenges and issues, resource optimization methods.